Probable recurrence of cardiac sarcoidosis in a transplanted heart - Matthew Seplowe, DO; Shazli Khan, MD; Lakshmisree Vemulakonda, MD; Fouzia Shakil, MD; Liana Michaud, DO; Chhaya Aggarwal-Gupta, MD; Gregg Lanier, MD; Avi Levine, MD; Suguru Ohira, MD, PhD; David Spielvogel, MD; Alan Gass, MD; Stephen Pan, MD, MS (JHLT Open)
Recurrence of cardiac sarcoidosis (CS) in post-transplant patients presents a rare but potentially life-threatening form of graft dysfunction and poses challenges due to varying clinical presentations, limited diagnostic modalities, and treatments based on anecdotal evidence. We discuss the case of a 46-year-old woman with CS, who developed cardiogenic shock necessitating orthotopic heart transplant. She subsequently developed likely recurrent CS in the transplanted heart. We discuss the rarity of this scenario as well as diagnostic modalities and management principles to consider.